2021
DOI: 10.1002/msc.1603
|View full text |Cite
|
Sign up to set email alerts
|

The systemic immunosuppressive effects of peripheral corticosteroid injections: A narrative review of the evidence in the context of COVID‐19

Abstract: Introduction Injected glucocorticoid's (corticosteroids) are commonly used in musculoskeletal practice. The current global COVID‐19 pandemic has increased attention on the potential for locally injected corticosteroids to exert a systemic immunosuppressive effect and the implications this may have in relation to COVID‐19 infection and vaccination. Aim This narrative review summarises the evidence regarding the potential systemic immunosuppressive effects of peripheral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Extensive counselling and written consent process including the discussion of the risks and benefits of the CSI prior to receiving the injection may have led to greater caution being shown by the participants and taking more precautions with regards to social contact and self‐isolation/distancing and carrying out more effective hand hygiene measures in the knowledge that the steroid can reduce the immune response. The findings of this study are consistent with and in keeping with other studies (Aziz et al., 2021 ; Bugeja et al., 2021 ; Chang et al., 2021 ; McKean et al., 2020 ; Morgan & Dattani, 2020 ; Newton et al., 2021 ; Regan et al., 2021 ). The risk identified within those studies demonstrated extremely low infection risk with very few or no positive cases of COVID‐19 infection following CSI.…”
Section: Discussionsupporting
confidence: 93%
“…Extensive counselling and written consent process including the discussion of the risks and benefits of the CSI prior to receiving the injection may have led to greater caution being shown by the participants and taking more precautions with regards to social contact and self‐isolation/distancing and carrying out more effective hand hygiene measures in the knowledge that the steroid can reduce the immune response. The findings of this study are consistent with and in keeping with other studies (Aziz et al., 2021 ; Bugeja et al., 2021 ; Chang et al., 2021 ; McKean et al., 2020 ; Morgan & Dattani, 2020 ; Newton et al., 2021 ; Regan et al., 2021 ). The risk identified within those studies demonstrated extremely low infection risk with very few or no positive cases of COVID‐19 infection following CSI.…”
Section: Discussionsupporting
confidence: 93%
“…Corticosteroids have well-known anti-inflammatory effects and generally suppress adaptive responses and enhance innate responses ( 99 ). The medical treatment of CRS mainly involves the application of topical, intranasal, and oral corticosteroids ( 100 ).…”
Section: Roles Of Epithelial Dysfunction In the Development Of Crsmentioning
confidence: 99%
“…Theoretically, GCIs may lead to short-term systemic immunosuppression, as it decreases the number of immune cells and cytokines for a few days and would therefore increase the risk of developing a bacterial or viral systemic infection, such as the COVID-19 infection. 5 However, this theoretical increased risk of developing a systemic infection did not translate into clinical findings. Two other retrospective studies found similar results and concluded that GCIs did not increase the likelihood of a COVID-19 infection.…”
Section: Systemic Infectionsmentioning
confidence: 99%
“…1,3,4 As the COVID-19 pandemic still represents a global concern, there are speculations that GCI could increase the likelihood of developing a COVID-19 infection because of its impact on the immune system. 5 The incidence rate of most of these systemic adverse effects and complications of GCI remains unclear in the medical literature.…”
Section: What Is Newmentioning
confidence: 99%
See 1 more Smart Citation